2022
DOI: 10.1002/ange.202209616
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis, Characterization, and Properties of Multi‐Element Nanoparticles

Abstract: Multi‐element nanoparticles (NPs) consisting of five or more elements have been increasingly studied in the past five years. Their emergence is taking materials science one step further because they exhibit superior properties to those of conventional NPs in a range of respects, including catalysis. This Review focuses on the recent progress in multi‐element NPs regarding synthesis, especially with regard to chemical synthesis, characterization, and properties. We begin with a brief introduction of multi‐eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…As structurally complex systems are now being handled with advanced characterization, the next challenge for the field will be accurately modeling nanoscale systems comprised of multiple elements. Multielement nanoparticles are selected to obtain synergistic effects and new properties altogether. , However, the spatial arrangement of the different elements impacts the resultant properties. For example, Woessner et al showed that the spatial distribution of Pd within/on branched Au nanoparticles with O h symmetry impacts their sensitivity to changes in refractive index .…”
Section: Challenge To the Field: Accurate Compositional Information I...mentioning
confidence: 99%
See 1 more Smart Citation
“…As structurally complex systems are now being handled with advanced characterization, the next challenge for the field will be accurately modeling nanoscale systems comprised of multiple elements. Multielement nanoparticles are selected to obtain synergistic effects and new properties altogether. , However, the spatial arrangement of the different elements impacts the resultant properties. For example, Woessner et al showed that the spatial distribution of Pd within/on branched Au nanoparticles with O h symmetry impacts their sensitivity to changes in refractive index .…”
Section: Challenge To the Field: Accurate Compositional Information I...mentioning
confidence: 99%
“…Multielement nanoparticles are selected to obtain synergistic effects and new properties altogether. 77,78 However, the spatial arrangement of the different elements impacts the resultant properties. For example, Woessner et al showed that the spatial distribution of Pd within/on branched Au nanoparticles with O h symmetry impacts their sensitivity to changes in refractive index.…”
Section: Compositional Information In Structural Modelsmentioning
confidence: 99%
“…In addition, the unique properties of nanoparticles (NPs), such as high catalytic activity due to a larger surface-to-volume ratio and unique local electronic states of the surface atoms, render them quite different from those of bulk materials. Therefore, the development of high-entropy nanomaterials can yield the fabrication of new types of materials, such as superior and highly stable catalysts. , …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of high-entropy nanomaterials can yield the fabrication of new types of materials, such as superior and highly stable catalysts. 7,8 Since the initial report by Rost et al, various studies of HEOs have been conducted. In the majority of these, the solidstate or sol−gel methods have been used as the synthetic method.…”
Section: ■ Introductionmentioning
confidence: 99%